Green-synthesized chromium oxide nanoparticles using pomegranate husk extract: Multifunctional bioactivity in antioxidant potential, lipase and amylase inhibition, and cytotoxicity - Cheah Shi-Yan; Aminuzzaman Mohammod; Phang You-Kang; Lim Sharon Chia-Yen; Koh Ming-Xiu; Djearamane Sinouvassane; Subramaniam Hemaroopini; Lim Boon-Hoe; Li Fang; Wong Ling-Shing; Tey Lai-Hock (Green Processing and Synthesis)
Malnutrition is a growing global health concern that contributes to obesity. This study presents the green synthesis of chromium oxide nanoparticles (Cr₂O₃ NPs) using pomegranate husk aqueous extract as both reducing and capping agents via a microwave-assisted method. The synthesized MA-Cr₂O₃ NPs were characterized using UV-Vis, FTIR, field emission scanning electron microscope, energy dispersive X-ray (EDX), HR-transmission electron microscopy (TEM), and X-ray diffraction methods. TEM analysis revealed an average particle size of 11.69 nm, and EDX confirmed nanoparticle (NP) purity. Antioxidant activity was assessed through 2,2′-diphenyl-1-picrylhydrazyl and ABTS assays, showing strong free radical scavenging abilities of 80.4% and 65.8% at 1 and 5 mg·mL−1, respectively. The NPs also contained notable levels of phenolics (10.14 mg GAE·g−1) and flavonoids (33.28 mg QE·g−1). In enzyme inhibition assays, NPs exhibited potent activity against pancreatic lipase (91.7%) and α-amylase (90.5%), with EC₅₀ values of 0.16 ± 0.002 mg·mL−1 and 0.15 ± 0.003 mg·mL−1 at 0.25 mg·mL−1. Cytotoxicity testing on Vero cells showed 55.5% viability at 0.25 mg·mL−1, indicating acceptable biocompatibility. These results highlight the potential of MA-Cr₂O₃ NPs for antioxidant and anti-obesity applications, offering a sustainable and eco-friendly solution for managing health issues related to malnutrition.